Studium parametrů přípravy a stabilizace belitu - Kohutová, Alice (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Předkládaná bakalářská práce je zaměřena na sledování chování minerálu belitu za vysokých teplot. Teoretická část se zabývá studiem podkladů přípravy a stabilizace C2S a jeho využití v nízkoenergetických cementech. Praktická část je zpracovaná formou rešerše vědeckých článků na dané téma a dosažených výsledků na FAST VUT, THD. Na základě dosavadních výzkumů je představen návrh a optimalizace metodiky přípravy polymorfu ß-C2S s následnou analýzou jeho čistoty a stability. Součástí práce je HT-XRD analýza, která umožňuje sledování fázových změn probíhajících při výpalu belitického slínku ve vysokoteplotní komoře.

The presented bachelor thesis is focused on monitoring the behavior of the mineral belite at high temperatures. The theoretical part deals with the study theories regarding the preparation and stabilization of C2S and its use in low-energy cements. The practical part is processed in the form of research of scientific articles dealing with the above mentioned topic and the results achieved at FAST BUT, THD. Based on previous research, there is introduced design and optimization of the methodology of preparation of polymorph ß-C2S, followed by analysis of its purity and stability. Part of the thesis is HT-XRD analysis, which allows monitoring of transformations during the burning of belite clinker in a high temperature chamber.
Study of Parameters of Preparation and Stabilization of Belite
Keywords: Dikalciumsilikát (Belit); ß-C2S; belitický cement; XRD analýza; vysokoteplotní komora; Dicalciumsilicate (Belite); ß-C2S; belite cement; XRD analysis; high temperature chamber